Fire and urban enviroment in early modern cities and towns of Croatian and Slavonian Kingdom - Petrić, Hrvoje, povjesničar (Array, 2008)
Summary: The author describes the theme of how great fires were instrumental in the creation of new urban developments in the early modern period. In Zagreb, for instance, very few buildings were made of fireproof materials. Most of the city’s buildings were made of timber and rooftops with wooden frames covered with wooden planks, tiles, or straw. The greatest fires in Zagreb communities occurred in the years 1624, 1645, 1674, 1706, and 1731. Threat of fire affected the spatial dispersion of the population and the construction of new streets with canals, which provided water for extinguishing fires. Due to a new building style which sought to use fireproof materials, cities established municipal brickyards. In order to have a fire alert system, cities also hired night watchmen, who appear in historical records as early as the seventeenth century